2017
DOI: 10.4081/monaldi.2017.831
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of life and functional capacity after lung transplantation: A single-center experience

Abstract: Lung transplantation (LT) increases the life expectancy of patients affected by end stage pulmonary disease; specifically, its ultimate aims are to improve survival and health related quality of life (HRQoL). The aim of the present longitudinal study was to determine the HRQoL trajectory and changes in functional capacity from time of entry in the waiting list for LT to 2 year after LT. The study included sixty-nine outpatients enrolled in a single medical center when they entered the waiting list for LT and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Specifically, results from longitudinal studies reported a significant improvement in the HRQoL in LTx-recipients, especially within the first six months post-transplant, with a relatively stable HRQoL thereafter [14,15]. Nonetheless, the individual trajectories of HRQoL over time are less clear in LTx-recipients, as their health is often hampered by numerous post-operative complications and the side effects of immunosuppressive therapy [16,17]. Indeed, few studies have examined distinct HRQoL trajectories within the same patients over time.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, results from longitudinal studies reported a significant improvement in the HRQoL in LTx-recipients, especially within the first six months post-transplant, with a relatively stable HRQoL thereafter [14,15]. Nonetheless, the individual trajectories of HRQoL over time are less clear in LTx-recipients, as their health is often hampered by numerous post-operative complications and the side effects of immunosuppressive therapy [16,17]. Indeed, few studies have examined distinct HRQoL trajectories within the same patients over time.…”
Section: Introductionmentioning
confidence: 99%
“…A similar finding was observed in the SF-36, which was used in four European studies on adult populations. 50 55 63 64 The instrument demonstrated robust reliability with Cronbach alpha of 0.95 64 and discriminated between CF and non-CF populations. 55 64 However, Abbott et al 50 found a high proportion of participants reporting no problems and that the instrument was less sensitive to clinical deterioration than the CFQoL.…”
Section: Resultsmentioning
confidence: 98%
“… 73 Other HRQoL surveys focused on mental health identified were the Patient Health Questionnaire-9, General Health Questionnaire and Generalised Anxiety Disorder-7. Each was used in one study and found to have acceptable reliability; 64 74 however, validity was not assessed.…”
Section: Resultsmentioning
confidence: 99%
“…The HRQoL survey was performed as a selfassessment by patients themselves using the SF-8, which is a shortened version of the SF-36 health survey. The SF-8 is the most popular assessment tool, and it is widely used for evaluating HRQoL related to many diseases [18,19]. Previous studies have confirmed the validity and reliability of the Japanese version of the SF-8 [20,21].…”
Section: Outcome Measuresmentioning
confidence: 99%